Formation and Development of Taproots in Deciduous Tree Species - Kościelniak, Paulina; Glazińska, Paulina; Kȩsy, Jacek; Zadworny, Marcin (Frontiers in Plant Science, 2021)
Trees are generally long-lived and are therefore exposed to numerous episodes of external stimuli and adverse environmental conditions. In certain trees e.g., oaks, taproots evolved to increase the tree’s ability to acquire water from deeper soil layers. Despite the significant role of taproots, little is known about the growth regulation through internal factors (genes, phytohormones, and micro-RNAs), regulating taproot formation and growth, or the effect of external factors, e.g., drought. The interaction of internal and external stimuli, involving complex signaling pathways, regulates taproot growth during tip formation and the regulation of cell division in the root apical meristem (RAM). Assuming that the RAM is the primary regulatory center responsible for taproot growth, factors affecting the RAM function provide fundamental information on the mechanisms affecting taproot development.